Does ROE Moderate the Impact of Temporary Shirkah Funds on SMEs Financing in Indonesia? - Arisnawati, Nur Fani (Share: Jurnal Ekonomi dan Keuangan Islam, 2024)
This study investigates the impact of temporary shirkah funds on the financing of Small and Medium Enterprises (SMEs) in Indonesia, using Bank Syariah Indonesia (BSI) as a sample. The Return on Equity (ROE) is utilized as a moderating variable. Employing a quantitative approach, secondary data was collected from BSI’s quarterly reports on the Indonesia Stock Exchange for the period of 2019-2021. The data was analyzed using Moderated Regression Analysis (MRA) with the Eviews 9 application. The results indicate that temporary syirkah funds have a significant partial effect on SMEs financing. However, ROE does not moderate the relationship between temporary syirkah funds and SMEs financing in BSI. These findings provide valuable insights for future researchers to further explore SME financing and highlight the importance of government support for Islamic banks in their efforts to finance SMEs, given the crucial role these enterprises play in the real sector and in bolstering the Indonesian economy. This study contributes to the growing body of literature on Islamic finance and SME financing, offering practical implications for policymakers and Islamic financial institutions.========================================================================================================ABSTRAK – Apakah ROE Memoderasi Pengaruh Dana Syirkah Temporer terhadap Pembiayaan UKM di Indonesia? Penelitian ini mengkaji pengaruh dana syirkah temporer terhadap pembiayaan Usaha] Kecil dan Menengah (UKM) di Indonesia dengan sampel pada Bank Syariah Indonesia (BSI) sementara Return on equity (ROE) dijadikan sebagai variabel moderasi. Menggunakan pendekatan kuantitatif, data penelitian dikumpulkan dari laporan triwulanan BSI di Bursa Efek Indonesia (BEI) untuk periode 2019-2021. Data dianalisis menggunakan Moderated Regression Analysis (MRA) dengan aplikasi Eviews 9. Hasil penelitian menunjukkan bahwa dana syirkah temporer memiliki pengaruh parsial yang signifikan terhadap pembiayaan UKM, tetapi ROE tidak memoderasi hubungan antara dana syirkah temporer dengan pembiayaan UKM di Bank Syariah Indonesia. Temuan ini dapat menjadi dasar bagi peneliti selanjutnya untuk lebih mengeksplorasi pembiayaan UKM dengan fokus urgensi dukungan pemerintah bagi bank syariah dalam pembiayaan UKM, mengingat peran penting yang dimainkan oleh usaha-usaha ini di sektor riil dan dalam mendorong perekonomian Indonesia. Studi ini berkontribusi terhadap pengembangan literatur tentang keuangan syariah dan pembiayaan UKM, memberikan implikasi praktis bagi pembuat kebijakan dan lembaga keuangan syariah.